Beyond demographics: Differences in patient activation across new immigrant, diverse language subgroups - Lubetkin, Erica I. (2014)
BACKGROUND: The federal government promotes “patient-centered medical homes” to plan care with respect to patients’ cultures and values and support patients’ self-care efforts. To promote self-care, the medical home would be best utilized by activated, engaged patients. OBJECTIVE: To measure and compare patient activation scores in English-, Spanish-, and Haitian-Creole speaking patients seen at an inner-city hospital ambulatory care practice. METHODS: Patient activation was measured using the Patient Activation Measure (PAM). RESULTS: Mean PAM scores and activation levels differed according to survey language (p<.001). US-born participants had higher mean PAM scores than persons born outside of the US. Participants living in the US longer had higher mean PAM scores than participants newer to the US. Levels of activation and mean PAM scores increased with greater comfort reading, speaking, and thinking in English. The mean PAM (SD) score of 61.5 (16.5) for Haitian-Creole speaking Caribbean Blacks was significantly lower than the mean PAM score of 68.8 (15.6) for English-speaking Caribbean Blacks (p-value= 0.006). Although mean PAM scores did not significantly differ between Haitian Creole and Spanish speakers, PAM stages differed according to language of survey completion (p<0.001), with a greater percentage of Haitian Creole speakers being categorized as stage I (least activated) as well as stage 4 (most activated). CONCLUSIONS: Spanish and Haitian Creole speakers have lower mean PAM scores than English speakers. Mean PAM scores did not differ between Hispanics and non-Hispanics or according to race, illustrating the need to examine the role of language and culture on patient activation.